REKAM JEJAK MALCOLM X DALAM PENEGAKAN HAK SIPIL ORANG KULIT HITAM AMERIKA SERIKAT 1957-1965 - Ari Kamal Malik; Wawan Darmawan (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2017)
This reasearch entitled “Peranan Malcolm X Dalam Perjuangan Hak-Hak Sipil Orang Kulit Hitam Tahun 1957-1965”. The method that used is hirostical method that divided into four steps, those are: heuristics, critique, interpretation and historiography as the tools to collecting data the researcher doing the study techniques with literature review that are relevant to the theme of this research. Based on the results of the study can be explained that Malcolm X or Ell-Haj Malik Ell-Shabbazz is the civil right struggle of blackcs who are quite notable, beside from being a struggler from the black civil rights, he also transformed as an Islamic figure of USA. So many ways that was struggled by Malcolm X to get the civil right of blacks, those are: created the relationship with another leader in the other country such as Kasem Gulick the leader of the Turkish parliament, and make the organization African American unity, attended in Asian African Conferenced in Bandung, make the Malcolm X Foundation. The struggles by Malcolm X are influenced from some prominent figure such as W.E.B Du Bois and Elijah Muhammad. The life of blacks is being well after struggling the civil right that was achieved by Malcolm X, the life of blacks began to rise after the struggles of the civil right by Malcolm X, the level of blacks began to increase, the various employment be able for blacks, the social facilities are not be differentianted, and the rights of election strated evenness.